Indirect British Rule, State Formation, and Welfarism in Kerala, India, 1860-1957 - Manali Desai (Social Science History 29:3 (fall 2005), 457-88, 2005)
This article examines the relationship between a strong nineteenth-century welfarist expansion between the 1860s and early 1940s, in Kerala, India, under indirect British rule, and the ``exceptional'' antipoverty regime that democratically elected Communists implemented during the postcolonial (post 1947) era in the state.While much attention has focused on Kerala as a model of social development and on postindependence state policies in creating it, no single work has attempted to understand the significance of its prior legacy of welfare.This article uses methods of comparative historical sociology to trace the historical making of Kerala's ``exceptionalism.'' It argues that the early welfare policies in Kerala were implemented in a dependent colonial context and aimed at warding off annexation by the British, but their unintended consequences were to stimulate what they were precisely designed to avoid-radical caste and class movements. The analysis suggests that the form and content of welfare policies are shaped by the exigencies of state formation, as state autonomy theorists would argue; however, it shows that political struggles are the decisive determining factors of the former.